Pencegahan Perilaku Sedentary Lifestyle Pada Remaja di SMA N 1 Tuntang - Fiki Wijayantii; Trimawati Trimawati; Mona Saparwati (Jurnal Pengabdian Ilmu Kesehatan, 2024)
Sedentary lifestyle is a type of lifestyle of individuals or groups that does not allow regular physical activity, a group of behaviors characterized by little or no physical movement and low energy expenditure of less than 1.5 MET (Metabolic Equivalent Task), MET is used to assess energy expenditure during activities. Sedentary behavior is a risky behavior for obesity in teenagers, heart disease and even affects life expectancy. Many factors can improve a sedentary lifestyle, including technological advances, demographic factors (age and gender), ethnicity and socio-economic status. The rapid development of technology makes teenagers passive. Rapid advances in technology have led to an increase in the sedentary lifestyle. Community service activities are carried out through stages of measuring knowledge data before and after providing health education, delivering material on preventing sedentary lifestyle behavior in teenagers. The result of this community service activity is an increase in teenagers' knowledge about the sedentary lifestyle. It is hoped that for students there will be a decrease in sedentary lifestyle after counseling on sedentary lifestyle behavior for teenagers at SMA N 1 Tuntang.